solve 2x2 12x − 14 = 0 by completing the square. 2(x 6)2 = 26; x = −6 square root 13, x = −6 − square root 132(x 6)2 = 20; x = −6 square root 20, x = −6 − square root 202(x 3)2 = 32; x = 1, x = −72(x 3)2 = 32; x = 13, x = 19

Respuesta :

assuming that the blank space is a plus
2x^2+12x-14=0

isolate x
(2x^2+12x)-14=0
undistribute 2
2(x^2+6x)-14=0
take 1/2 of 6 and square and add negative and positive
2(x^2+6x+9-9)-14=0
factor perfect squrae
2((x+3)^2-9)-14=0
distribute
2(x+3)^2-18-14=0
2(x+3)^2-32=0
2(x+3)^2=32
divide 2
(x+3)^2=16
sqrt
x+3=+/-4
minus 3
x=+/-4-3
x=-7 or 1
2nd to last option

Answer:

c - 2(x + 3)2 = 32; x = 1, x = −7